Path Analysis on the Factors Associated with Consistent Use of Female Condom among Female Sex Workers in Surakarta - Rizka Ayu Setyani; Ari Natalia Probandari; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Female condom is an alternative method to prevent HIV/ AIDS transmission. However, its utilization is low and scanty among female sex workers. It is important to have knowledge on the factors that determine female condom use. This study aimed to determine the factors associated with the acceptance and use of female condom among female sex workers in Surakarta.Subjects and Method: It was an analytic and observational study using case control design. The study was conducted at a prostitution area in Surakarta, Central Java, from August to September 2016. A total of 230 female sex workers consisting of 110 female sex workers who used female condoms and 120 female sex workers who did not use female condoms, was selected purposively in this study. The dependent variables were acceptance and use of female condom. The independent variables were sex partner support, peer educator support, and pimp support. The data were collected by a set of questionnaire and analyzed by path analysis model.Results: Acceptance of female condom was associated with its use among female sex workers (b = 0.30; p < 0.001). Peer educator support was associated with acceptance of female condom (b = 0.06; p < 0.001). Peer educator support (b = 0.03; nilai p = 0.012) and sex partner support (b = 0.05; p = 0.042). The association between acceptance of female condom and pimp support was not statistically significant (p = 0.133).Conclusion: Peer educator support and sex partner support have direct association with both acceptance and use of female condom among female sex workers. Keywords: path analysis, support, sex partner, peer educator, consistant use, female condom, female sex workersCorrespondence: Rizka Ayu Setyani. School of Midwivery, Respati University, Yogyakarta. Email: bidanrizkaayusetyani@gmail.comJournal of Health Promotion and Behavior(2016), 1(2): 120-126https://doi.org/10.26911/thejhpb.2016.01.02.07